Fast determination of five chiral antipsychotic drugs using dispersive liquid–liquid microextraction combined with capillary electrophoresis. Issue 15 (31st March 2020) - Hsieh, Ming-Mu; Chiu, Tai-Chia; Chen, Szu-Hua
Abstract : This study developed a new method for the extraction, clean up, chiral separation, and determination of five pairs of phenothiazine drugs using ultrasound-assisted dispersive liquid–liquid microextraction combined with capillary electrophoresis. Abstract : This study developed a new method for the extraction, clean up, chiral separation, and determination of five pairs of phenothiazine drugs using ultrasound-assisted dispersive liquid–liquid microextraction combined with capillary electrophoresis (CE). A mixture of extraction solvent (30 μL of CHCl3 ) and dispersive solvent (200 μL of tetrahydrofuran) was rapidly injected using a syringe, which formed tiny cloudy droplets of an organic extractant that dispersed entirely into the aqueous phase. After centrifuging, the sediment phase of volume 60 ± 0.5 μL was transferred into a small vial and evaporated to dryness. The residue was reconstituted in 5 μL of aqueous solution, analyzed using CE and then successfully baseline separated in 6 min using a background electrolyte composed of 5 mM hydroxypropyl-γ-cyclodextrin, 0.9% poly(diallyldimethylammonium chloride), and 150 mM tris-formate at pH 3.0. The developed method was linear in the 0.01–10 μM range, with R 2 ≥ 0.9956 for all target analytes. The limit of detection (S/N = 3) and the limit of quantification (S/N = 10) were 2–4 nM and 10 nM, respectively. Excellent repeatability (RSD ≤ 5.5%, n = 5) was achieved. The recoveries of all phenothiazine drugs from urine were in the 83.5–104.0% range. The advantages of this approach were low cost, versatility, simplicity, and high sensitivity.